Sosialisasi parenting: tanamkan kesadaran kurangi resiko bahaya pacaran - Saputri, Afif Berlian (Maliki Interdisciplinary Journal, 2026)
Dating has become a commonplace in life, and there are many dangers of dating that have occurred in Indonesia and even the world. Therefore, we held a parenting socialization with the theme of instilling awareness and reducing the risks of dating. The goal was to inform students about the many dangers of dating, making them aware and reducing the prevalence of dating in Indonesia. Free association is like a tempting maze, but it harbors hidden dangers. Its negative impacts are like a time bomb ready to explode and destroy the future of teenagers. Impaired health, declining academic performance, social problems, threatened family harmony, and a bleak future are just a few of the consequences that must be borne. The root of the problem of free association is like a complex and interconnected tangled thread. Lack of knowledge about the dangers of free association, social pressure from peers, psychological and emotional problems, lack of attention and affection from family, and easy access to illegal drugs and other addictive substances are factors that push teenagers into falling into it.